Funding of medical education: the need for transparency - Dacre, Jane (Clin Med (Lond), 2013)
Medical education is vital to the future of healthcare provision. It is also expensive. We should ensure that the funding spent on medical education is spent in the most cost-effective way possible and delivers the best possible returns on our investment. Budgets that have been allocated to medical education should be spent on this and not on research or clinical care. Educational budgets should be transparent – so that their use and misuse are clear. We should develop a culture of lifelong learning and continually make explicit that future healthcare professionals need investment in their education to maintain the quality and safety of healthcare delivery.